2018
DOI: 10.1016/j.ajpath.2018.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Exosomes and Exosomal CCL2 mRNA as Biomarkers of Active Histologic Injury in IgA Nephropathy

Abstract: IgA nephropathy (IgAN) features variable renal pathology and a heterogeneous clinical course. Our aim was to search noninvasive biomarkers from urinary exosomes for IgAN patients; membrane nephropathy and minimal change disease were included as other glomerulopathy controls. Transmission electron microscopy and nanoparticle tracking analysis confirmed the size and morphology characteristic of urinary exosomes. Exosome markers (Alix and CD63) as well as renal cell markers [aquaporin 2 (AQP2) and nephrin] were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 31 publications
(31 reference statements)
1
58
0
1
Order By: Relevance
“…Further study showed that CD2AP mRNA from exosome was correlated with both kidney function and severity of fibrosis . Importantly, urinary exosomes and exosomal CCL2 mRNA are promising biomarkers reflecting active renal histologic injury and predicting renal function deterioration in IgAN …”
Section: Ev As Biomarkers In Kidney Diseasementioning
confidence: 96%
See 1 more Smart Citation
“…Further study showed that CD2AP mRNA from exosome was correlated with both kidney function and severity of fibrosis . Importantly, urinary exosomes and exosomal CCL2 mRNA are promising biomarkers reflecting active renal histologic injury and predicting renal function deterioration in IgAN …”
Section: Ev As Biomarkers In Kidney Diseasementioning
confidence: 96%
“…72 Importantly, urinary exosomes and exosomal CCL2 mRNA are promising biomarkers reflecting active renal histologic injury and predicting renal function deterioration in IgAN. 73 Moreover, the stability and enrichment of miRNA in exosome make it a promising candidate biomarker for kidney disease. Exosome miRNA was stable despite repeated frozen-thaw cycles and long-term storage.…”
mentioning
confidence: 99%
“…For example, level of urinary exosomal miR-193a was greater in children with primary focal segmental glomerulosclerosis as compared to those with minimal change nephrotic syndrome (NS) . Urinary exosomal excretion and chemokine (C-C motif) ligand-2 (CCL2) mRNA level were increased in IgA nephropathy and correlated with the disease activity (Feng et al, 2018). Additionally, 30 urinary exosomal miRNAs were markedly increased in children with idiopathic NS .…”
Section: Lupus Nephritis and Other Glomerular Diseasesmentioning
confidence: 99%
“…This property positions EV as a potential source for the discovery of novel biomarkers of different diseases. In this regard, the urinary exosome has been reported to be a novel biomarker for renal disease [207][208][209]. Moreover, the stability and enrichment of miRNA in the exosome make it a promising candidate as a biomarker for different glomerular diseases [210][211][212][213][214][215].…”
Section: Therapeutic Potential Of Chronic Glomerular Diseases By Restmentioning
confidence: 99%